Public wash programs, long-run child development, and intergenerational mobility: New evidence from rural People's Republic of China - Dongqin Wang; Eddy Weijian Zou (Asian Development Bank Institute (ADBI), 2023)
Using individual-level longitudinal data from 1989 to 2015, we examine the long-run effects of nationwide water plant construction and household-level toilet subsidy programs in rural People's Republic of China (PRC) on children's education, health, and nutrition. We exploit the differential timing of these programs across rural villages and use a generalized difference-in-differences strategy to estimate their long-run effects. We find that each program independently increased years of schooling up to 20 years after its implementation. Effects on education are larger for girls than for boys, and for toilet subsidy programs. On average, toilet (water) improvement increases years of schooling by 0.608 (0.341) for girls and 0.405 (0.260) for boys. We find evidence that the toilet program had larger education effects if it was introduced after the water program. Exploiting differential program exposure by birth cohorts, we show that improving child health is an underlying mechanism toward enhanced education effects. We then investigate how the programs affected intergenerational education persistence. The toilet program significantly reduced maternal-child education persistence, while improving the upward education mobility of exposed children. Our findings suggest that improving household sanitation has larger educational benefits than expanding access to safe drinking water and that public WASH programs can be effective in reducing intergenerational inequality in socioeconomic outcomes.
Keywords: I18; I24; J24; J13; 330; sanitation; water and toilet improvements; health and human capital; child development; education; intergenerational mobility; rural People's Republic of China